Eficacia y validez jurídica de la expedición de actos administrativos por medios electrónicos (2015)
In Colombia, more than a decade the use of electronic media in order to obtain the improvement of the administrative activity, as a tool to ensure, inter alia, access and disclosure of proceedings against the State was regulated citizens. With the emergence of Act 527 of 1999 defined and regulated access and use of data messages, electronic commerce, digital signatures and certification bodies and items for the issuance of an administrative act were established by electronic means; however, only until 2011, with the issuance of the Code of Administrative Procedure and Administrative Disputes Act 1437 of 2011, fundamentals such as notification, publication and procedure required for the valid issuance of administrative acts by electronic means are configured , which were already regulated in the Law 527 of 1999. It is observed so that the constant social evolution and the incessant emergence of new technologies, for which it is necessary to go to formalize and regulate its scope by systems organizational political, leading to that state activity is the need to be creating specific parameters and controls and specialized for every new phenomenon born as a mechanism to avoid the lag of the rule against those. Also, sometimes the same State must resort to these scientific and technological advances; adapt and introduce management structure in order to make more efficient and effective function by government culturización online.